Shifts in sensory neuron identity parallel differences in pheromone preference in the European corn borer - Koutroumpa, Fotini A.; Kárpáti, Zsolt; Monsempes, Christelle; Hill, Sharon R.; Hansson, Bill S.; Jacquin-Joly, Emmanuelle; Krieger, Jürgen; Dekker, Teun (Frontiers in Ecology and Evolution, 2014)
Pheromone communication relies on highly specific signals sent and received between members of the same species. However, how pheromone specificity is determined in moth olfactory circuits remains unknown. Here we provide the first glimpse into the mechanism that generates this specificity in Ostrinia nubilalis. In Ostrinia nubilalis it was found that a single locus causes strain-specific, diametrically opposed preferences for a 2-component pheromone blend. Previously we found pheromone preference to be correlated with the strain and hybrid-specific relative antennal response to both pheromone components. This led to the current study, in which we detail the underlying mechanism of this differential response, through chemotopically mapping of the pheromone detection circuit in the antenna. We determined that both strains and their hybrids have swapped the neuronal identity of the pheromone-sensitive neurons co-housed within a single sensillum. Furthermore, neurons that mediate behavioral antagonism surprisingly co-express up to five pheromone receptors, mirroring the concordantly broad tuning to heterospecific pheromones. This appears as possible evolutionary adaptation that could prevent cross attraction to a range of heterospecific signals, while keeping the pheromone detection system to its simplest tripartite setup.